Measurement and conceptualization of male involvement in family planning: a bibliometric analysis of Africa-based studies - Tosin Olajide Oni; Rebaone Petlele; Olufunmilayo Olufunmilola Banjo; Akinrinola Bankole; Akanni Ibukun Akinyemi (BMC, 2024)
Abstract Background Male involvement in Family Planning (FP) is an exercise of men's sexual and reproductive health rights. However, the measurement of male involvement has been highly inconsistent and too discretional in FP studies. As a result, we used bibliometric tools to analyze the existing measures of male involvement in FP and recommend modifications for standard measures. Methods Using developed search terms, we searched for research articles ever published on male involvement in FP from Scopus, Web of Science, and PubMed databases. The search results were filtered for studies that focused on Africa. A total of 152 research articles were selected after the screening, and bibliometric analysis was performed in R. Results Results showed that 54% of the studies measured male involvement through approval for FP, while 46.7% measured it through the attitude of males to FP. About 31% measured male involvement through input in deciding FP method, while others measured it through inputs in the choice of FP service center (13.6%), attendance at FP clinic/service center (17.8%), and monetary provision for FP services/materials (12.4%). About 82.2% of the studies used primary data, though the majority (61.2%) obtained information on male involvement from women alone. Only about one in five studies (19.1%) got responses from males and females, with fewer focusing on males alone. Conclusion Most studies have measured male involvement in FP through expressed or perceived approval for FP. However, these do not sufficiently capture male involvement and do not reflect women's autonomy. Other more encompassing measures of male involvement, which would reflect the amount of intimacy among heterosexual partners, depict the extent of the exercise of person-centered rights, and encourage the collection of union-specific data, are recommended.